Rekonstruksi Narasi Sejarah di Era Digital: Inovasi Pembelajaran Sejarah Melalui Gamifikasi, Kecerdasan Buatan, dan Learning Management System - Dhalia Soetopo; Miskawi Miskawi; Andini Ramadhani; Risma Maulin Fitriyani; Irsyad Arjuna Valentino Mesy Syah Putra (Medan Resource Center, 2026)
The perception of history learning as a memorization-oriented and monotonous subject remains a significant challenge in the digital era. This condition requires innovative pedagogical approaches that align with the learning characteristics of Generation Z and Generation Alpha, who are highly engaged with digital technology. This community service program aimed to strengthen history teachers' competencies in reconstructing historical narratives through the integration of gamification, Artificial Intelligence (AI), and Learning Management Systems (LMS). The program was conducted on May 22, 2026, at Universitas PGRI Banyuwangi and history teachers. The training employed an experiential learning approach consisting of three sessions: historical gamification, AI-assisted instructional material development using NotebookLM, and digital classroom management through an LMS. Program effectiveness was evaluated using pre- and post-training assessments, observations, and participant feedback. The results indicated an increase in participants' digital pedagogical competence successfully designed technology-enhanced history learning activities integrating gamification, AI, and LMS. Participants also demonstrated improved confidence in developing interactive and student-centered learning experiences while maintaining historical accuracy. These findings suggest that integrating gamification, AI, and LMS effectively enhances teachers' digital competencies and supports more engaging, meaningful, and innovative history learning in the digital era.